Case reportPseudo-stroke manifestation of multiple myeloma: a report of two cases with literature review - Czapiewski, Piotr; Szmuda, Tomasz; Dzierżanowski, Jarosław; Słoniewski, Paweł; Sworczak, Krzysztof; Gnacińska, Maria; Dubaniewicz-Wybieralska, Mirosława; Hellmann, Andrzej; Biernat, Wojciech (Folia Neuropathologica, 2013)
Multiple myeloma rarely presents with neurological symptoms. We describe two patients with pseudo-stroke manifestation of multiple myeloma. The first patient was a 60-year-old female with the initial presentation of multiple myeloma forming a large skull tumour compressing the brain with resultant symptoms of aphasia, limited logical contact and right upper extremity paresis. The second patient was a 69-year-old female who presented with a partial motor epileptic seizure involving both right limbs with persisting weakness of muscles and speech disturbances due to a skull tumour 4 years after the diagnosis of multiple myeloma. Pseudo-stroke manifestation of multiple myeloma is extremely uncommon, however it can sometimes be observed both as an initial presentation and in the course of long-lasting disease.